2018
DOI: 10.1038/s41467-018-05990-z
|View full text |Cite
|
Sign up to set email alerts
|

Ribitol restores functionally glycosylated α-dystroglycan and improves muscle function in dystrophic FKRP-mutant mice

Abstract: O-mannosylated α-dystroglycan (α-DG) serves as receptors for cell–cell and cell–extracellular matrix adhesion and signaling. Hypoglycosylation of α-DG is involved in cancer progression and underlies dystroglycanopathy with aberrant neuronal development. Here we report that ribitol, a pentose alcohol with previously unknown function in mammalian cells, partially restores functional O-mannosylation of α-DG (F-α-DG) in the dystroglycanopathy model containing a P448L mutation in fukutin-related protein (FKRP) gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 48 publications
4
69
0
2
Order By: Relevance
“…The authors showed that the mutant protein was able to restore the α‐DG glycosylation at the muscle membrane and correction of the dystrophic phenotype when overexpressed by adeno‐associated virus (AAV) injection in a P448L neo− mouse model. In addition, in a more recent study, the same group showed that supplementation of ribitol in drinking water of the P448L neo− mouse increased α‐DG glycosylation (Cataldi, Lu, Blaeser, & Lu, ), indicating that even the endogenous P448L mutant protein present in the mice might still retain some level of functionality. Altogether, these different pieces of evidence support the idea that a pharmacological strategy allowing a bypass of the QC might lead to a therapeutic benefit for patients with the corresponding genetic variants.…”
Section: Discussionmentioning
confidence: 99%
“…The authors showed that the mutant protein was able to restore the α‐DG glycosylation at the muscle membrane and correction of the dystrophic phenotype when overexpressed by adeno‐associated virus (AAV) injection in a P448L neo− mouse model. In addition, in a more recent study, the same group showed that supplementation of ribitol in drinking water of the P448L neo− mouse increased α‐DG glycosylation (Cataldi, Lu, Blaeser, & Lu, ), indicating that even the endogenous P448L mutant protein present in the mice might still retain some level of functionality. Altogether, these different pieces of evidence support the idea that a pharmacological strategy allowing a bypass of the QC might lead to a therapeutic benefit for patients with the corresponding genetic variants.…”
Section: Discussionmentioning
confidence: 99%
“…Several promising approaches are being investigated to restore functional glycosylation of α-DG using available FKRP-mutant mouse models [16][17][18][19][20][21][22]. One strategy is to increase the levels of metabolites involved in the FKRPmediated α-DG glycosylation process, such as ribitol treatment [16,23], which has been shown to rescue α-DG functional glycosylation in FKRP P448L mice. Nevertheless, this promising result needs further investigation to determine if this beneficial effect can be extended to other FKRP mutations, and if ribitol treatment presents any detrimental side effects.…”
Section: Introductionmentioning
confidence: 99%
“…This is an essential enzymatic step for the post-translational installation of matriglycans on αDG, which are the structural basis for αDG-ligand binding [4]. Recently, dietary supplementation with ribitol was shown to improve muscle phenotypes in a mouse model of FKRP-related dystroglycanopathy [5].…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of ISPD mutant cells with ribitol or CDP-ribitol promotes αDG glycosylation [13, 27], and dietary ribitol supplementation rescues muscle phenotypes in Fkrp mutant mice [5]. Here, we extend this concept from animal models to a human patient-derived system.…”
Section: Discussionmentioning
confidence: 99%